Management of Dry Eye Syndrome Through Ayurvedic Interventions: An In-Depth Analysis (International Journal of Ayurveda and Pharma Research, 2023)
Dry eye syndrome (DES) is a chronic ocular condition characterized by reduced tear production or increased tear evaporation, leading to discomfort, visual disturbances, and potential damage to the ocular surface. Conventional treatments like artificial tears provide temporary relief without addressing the underlying causes. This article explores the potential of Ayurvedic interventions in managing DES by drawing parallels with "Shushkashipaka," an Ayurvedic ocular surface disease with similar manifestations. Ayurveda offers various Kriyakalpa procedures such as Tarpana, Putpaka, Parisheka, Ashchyotana, Nasya, and Anjana, which can help address the multifactorial nature of DES. These personalized and comprehensive approaches provide alternative and complementary therapeutic options for managing DES. Further research and clinical studies are needed to validate the efficacy and safety of Ayurvedic interventions in managing DES. However, the principles and therapeutic procedures described in Ayurvedic texts hold promise in addressing this prevalent eye condition.